A Comparative Analysis of the Labour Market Performance of University-Educated Immigrants in Australia, Canada, and the United States: Does Policy Matter? - Andrew Clarke; Ana Ferrer; Mikal Skuterud (Institute of Labor Economics (IZA), 2018)
We examine data from Australia, Canada, and the U.S. to inform the potential for immigrant screening policies to influence the labour market performance of skilled immigrants. Our estimates point to improvements in employment rates and weekly earnings of male university-educated immigrants in all three countries concomitant with skilled immigration policy reforms. Nonetheless, the gains are modest in comparison to a substantial and persistent performance advantage of U.S. skilled immigrants. Given that there is increasingly little to distinguish the skilled immigration policies of these countries, we interpret the U.S. advantage as primarily reflecting the relative positive selectivity of U.S. immigrants.
Keywords: J24; J15; J08; 330; skilled migration; immigrant selection policies; immigrant labour market performance